TACE Versus TARE in the Treatment of Liver-Metastatic Breast Cancer: A Systematic Review - Charalampos Lalenis; Alessandro Posa; Valentina Lancellotta; Marcello Lippi; Fabio Marazzi; Pierluigi Barbieri; Patrizia Cornacchione; Matthias Joachim Fischer; Luca Tagliaferri; Roberto Iezzi (Tomography)
Background/Objectives: Liver metastases are common among patients with breast cancer and have a poor prognosis if left untreated. The aim of this systematic review is to evaluate and compare chemoembolization (TACE) versus radioembolization (TARE) treatments in patients with breast cancer liver-dominant metastases in terms of overall survival (OS), local tumor control (LC), and toxicity. Methods: The S.P.I.D.E.R framework was used to address the clinical question. A systematic literature search using PubMed and Scopus was performed to identify full articles evaluating the efficacy of TACE and TARE in patients with liver metastases from breast cancer. Results: The literature search resulted in 10 articles for TACE, 13 articles for TARE and 1 for combined TACE/TARE, totaling 462 patients for the TACE group and 627 for the TARE group. The median LC was 68.7% for TACE and 78.9% for TARE. The median OS was 15.3 months for TACE and 11.9 for TARE. Progression at three months was 32.5% for TACE and 20.6% for TARE. Conclusions: The included studies were heterogeneous, varying widely in design, patient selection, and therapeutic protocols. Nonetheless, this systematic review suggests that locoregional therapies are effective in the treatment of liver metastases in patients with breast cancer and may improve tumor burden, alleviate symptoms and extend overall survival. The median LC of the liver metastases at three months was higher in the TARE group compared to TACE. However, the TARE group showed lower OS rates after treatment.